THE MANDATORY USE OF NATIONAL LANGUAGE IN INDONESIA AND BELGIUM: AN OBSTACLE TO INTERNATIONAL CONTRACTING? - Penasthika, Priskila Pratita (UI Scholars Hub, 2019)
Law Number 24 of 2009 on National Flag, Language, Emblem, and Anthem of Indonesia requires that any contract involving an Indonesian party must be drafted in Indonesian. In applying this law, the Supreme Court of the Republic of Indonesia, in Nine AM v. PT Bangun Karya Pratama Lestari judgment, annulled a loan agreement because it was considered to violate the language requirement. Although claiming to strengthen the use of Indonesian language in a contract, this judgment underscores a potential risk of voidance a foreign party face in entering into an agreement drafted in a foreign language when contracting with an Indonesian counterparty. On the other side of the hemisphere, the Court of Justice of the European Union in Anton Las v. PSA Antwerp NV and New Valmar BVBA v. Global Pharmacies Partner Health Srl drew the public attention to the obligation to use Dutch in employment contract and company documents as imposed in the Dutch-speaking region of Belgium. Despite Indonesia and Belgium being geographically far from each other, the abovementioned judgments underline the phenomenon that national language still plays an important role in influencing cross-border legal relations. This article seeks to explore the legal impacts of the obligation to use national language in contracts has on freedom of parties to contracting. It further argues that this obligation impedes international contracting.